Pemanfaatan IoT Pada Sistem Atap Otomatis Berdasarkan Cuaca dan Waktu Terintegrasi Aplikasi Telegram Berbasis NodeMCU - Mohammad Faizal; Alvino Octaviano (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Tepi Lereng Coffee Shop is a modern Coffee shop located in Pamulang, South Tangerang which is a place to do collage assignment, meeting discussions, gathering place and of course enjoying coffee. Unpredictable weather conditions make it a problem for Tepi Lereng Coffee Shop business owner who carries the concept of semi-outdoor cafe when it rains, these conditions make it difficult for visitors who come to find the shelter. The Purpose of this research is to help activities and effectiveness of Tepi Lereng Coffee Shop employees and customers and designing a NodeMCU microcontroller that is connected to the LDR sensor, Raindrop sensor, servo motor and controls the Roof using Telegram to run optimally. Method used is Prototype Method, this method used approach to making a design quickly and gradually so that it can be immediately evaluated by potential users/clients. With Prototype Method developer and client can interact with each other during the system design process. With the automatic roof system integrated with the NodeMCU-based Telegram application, it can reduce the worry of the Tepi Lereng Coffee business owner when the weather is hot or rainy.